PENGKAJIAN POTENSI DESA DENGAN PENDEKATAN PARTISIPATIF DI DESA MAWAI INDAH KECAMATAN BATU AMPAR KABUPATEN KUTAI TIMUR - Sanusi, Herman; Hidayah, Abdul Kholik (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Assessment of Potential Rural Participatory Approach Mawai Indah Village District Batu Ampar East Kutai Regency.The purpose of this study was to determine the potential, problems and solving problems in the village Mawai Indah and planning activities that can be done on a village to village economic development based on the potential that exists in the village.The study is in the data collection methods of Participatory Rural Appraisal (PRA) while the data analysis using the SWOT method. PRA techniques used are Search History Village, Making Chart Trends and Changes in Livelihood, Preparation Calendar Season, Making Map/Sketch Village, Institutional Assessment (Venn Diagram), Chart Daily Activity and Village Transect. PRA is carried out by the villagers Mawai Indah themselves, District of Batu Ampar, East Kutai Regency.The results demonstrated the potential of the village in the form of land, a good pepper crop production, the existence of companies operating in the village and there are problems that occur such as the difficulty of marketing of agricultural/plantation pests and fusarium the pepper plants as well as frequent flooding. Problem solving is to work closely with the company to make a good plantation, accommodating production, improve HR community. Immediately complete the formation of village cooperatives, share experiences with other farmers cope with pests and fusarium as well as the activity of optimizing control dams owned Mawai Indah Village.